Inverse Ubbelohde effect in the short hydrogen bond of photosystem II: Relation between H/D isotope effect and symmetry in potential energy profile. Issue 23 (27th June 2016) - Kanematsu, Yusuke; Tachikawa, Masanori; Takano, Yu
Abstract : The short hydrogen bond between tyrosine Yz and D1‐His190 of photosystem II (PSII) was investigated using multicomponent quantum mechanics, where the quantum fluctuation of a hydrogen nucleus was incorporated into electronic structure calculation. Our computation demonstrated that the deuteration for hydrogen in the short hydrogen bond of PSII led to the reduction of the O…N distance. It indicated an inverse Ubbelohde effect typically recognized in strong and symmetric hydrogen‐bonding clusters such as FHF – and H 3 O 2 − . We confirmed that the relation between the geometric isotope effect and the symmetry of the potential energy profile of FHF – was reasonably agreed with that of PSII. According to this agreement, the short hydrogen bond in PSII can be regarded as a short strong hydrogen bond. © 2016 Wiley Periodicals, Inc. Abstract : H/D isotope effects on hydrogen bonds in Photosystem II (PSII) and in FHF – were computed using the multicomponent quantum mechanics. Both hydrogen bonds revealed decrements of donor–acceptor distances: inverse Ubbelohde effect, and also the dependence on the symmetry in the potential energy profiles. According to the agreement of the isotope effects, the hydrogen bond in PSII was confirmed as a biomolecular system containing the short strong hydrogen bond.